2007
DOI: 10.1088/0022-3727/41/1/015206
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the insulation characteristics of c-C4F8/CO2gas mixtures by the Monte Carlo method

Abstract: This paper analyses the insulation characteristics of c-C4F8/CO2 gas mixtures using the Monte Carlo method with the null-collision technique and studies the possibility of applying that in the gas insulation of power equipment. The density-normalized effective ionization coefficient (α − η)/N for c-C4F8/CO2 gas mixtures has been calculated using a sample of a pulsed Townsend discharge. The overall density-reduced electric field strength (E/N) could be varied between 150 and 450 Td (1 Td = 10−17 V cm2), while t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…However, due to its high boiling point (−8 • C), it should be used by mixing with CF 4 , N 2 , CO 2 , or air. The dielectric strength of c-C 4 F 8 /CO 2 is higher than that of SF 6 /CO 2 , and the GWP of c-C 4 F 8 /CO 2 is much lower than that of SF 6 /CO 2 [16]. Li et al [17] studied the dielectric strength of c-C 4 F 8 with CF 4 , CO 2 , N 2 , O 2 , and air mixture by Boltzmann equation.…”
Section: Perfluorocyclobutane (C-c 4 F 8 )mentioning
confidence: 99%
“…However, due to its high boiling point (−8 • C), it should be used by mixing with CF 4 , N 2 , CO 2 , or air. The dielectric strength of c-C 4 F 8 /CO 2 is higher than that of SF 6 /CO 2 , and the GWP of c-C 4 F 8 /CO 2 is much lower than that of SF 6 /CO 2 [16]. Li et al [17] studied the dielectric strength of c-C 4 F 8 with CF 4 , CO 2 , N 2 , O 2 , and air mixture by Boltzmann equation.…”
Section: Perfluorocyclobutane (C-c 4 F 8 )mentioning
confidence: 99%
“…Several other, perhaps minor, emissive uses of c-C 4 F 8 are also known (see Lewis, 1989;Chung and Bai, 2000;Harnisch, 2000;Christophorou and Olthoff, 2001;Kim et al, 2002;Liu et al, 2008; and reference therein), e.g., in aerolyzed foods, as a food packaging gas, in retinal detachment surgery, for contrast-enhanced ultrasound imaging, in radar systems, as a specialty refrigerant (e.g., in submarines where R405A (43 % c-C 4 F 8 ) can replace pure HCFC-22 and chlorofluorocarbon CFC-12), as an electrically insulating dielectric gas (e.g., in mixtures with sulfur hexafluoride, SF 6 ), as a medium for polymerization reactions, in fire extinguishers, to estimate the size of natural gas and oil reservoirs, for leak detection of nuclear waste containers (Schmidbauer, N., personal communication, 2011) and as a geohydrological tracer (Kass, 1998). Production of c-C 4 F 8 for these uses, via the pyrolysis of HCFC-22 or perhaps from 1,2-dichlorotetrafluoroethane (CFC-114) (Siegemund et al, 2016), may cause emissions as well.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the long lifetime and high radiative efficiency, emissions of c-C 4 F 8 (and other perfluorinated compounds) essentially permanently alter the radiative budget of Earth (Victor and MacDonald, 1999). Lovelock (1971) predicted the accumulation of c-C 4 F 8 in the global atmosphere, but to the best of our knowledge, the earliest atmospheric measurements of c-C 4 F 8 were presented in Sturges et al (1995) and in the PhD theses of Travnicek (1998) and Oram (1999, discussed further below). Sturges et al (2000) determined from one vertical balloon-borne profile in 1994 that c-C 4 F 8 mole fractions declined from ∼ 1.1 ppt (parts per trillion) in the lower atmosphere of the Northern Hemisphere (NH) to ∼ 0.6 ppt in the stratosphere, while Harnisch (1999) reported that Sturges et al (1995) had found 0.4 ppt in the troposphere decreasing to ∼ 0.1 ppt at 25 km in 1994, suggesting a revised calibration scale.…”
Section: Introductionmentioning
confidence: 99%
“…Several other, perhaps minor, emissive uses of c-C 4 F 8 are also known (see Lewis, 1989;Chung and Bai, 2000;Harnisch, 2000;Christophorou and Olthoff, 2001;Kim et al, 2002;Liu et al, 2008; and reference therein), e.g., in foamed/sprayed foods, as a food packaging gas, in retinal detachment surgery, for contrast-enhanced ultrasound imaging, in radar systems, as a specialty refrigerant (e.g., in submarines where R-405A (43 % c-C 4 F 8 ) can replace pure HCFC-22 and the chlorofluorocarbon CFC-12, CCl 2 F 2 ), as an electrically insulating dielectric gas (e.g., in mixtures with sulfur hexafluoride, SF 6 ), as a medium for polymerization reactions, in fire extinguishers, and perhaps as a geohydrological tracer (Kass, 1998). Several chemical reactions in which c-C 4 F 8 is used to introduce -CF 3 groups into organic molecules are known (https://scifinder.cas.org/, last access: 19 June 2019) as well as reactions leading to desirable products such as HFO-1234yf, a fourth-generation refrigerant used in newer mobile air conditions (MACs; see Supplement) or HFP, but also various other compounds.…”
Section: Introductionmentioning
confidence: 99%